Buckled Honeycomb Lattice Compound Sr3CaOs2O9Exhibiting Antiferromagnetism above Room Temperature - Thakur, Gohil S.; Hansen, Thomas C.; Schnelle, Walter; Guo, Shuping; Janson, Oleg; Van Den Brink, Jeroen; Felser, Claudia; Jansen, Martin (Chemistry of Materials, 2022)
Synthesis, crystal structure, and magnetic properties of a new 2:1 ordered triple perovskite Sr3CaOs2O9 are reported. The compound crystallizes in a P21/c space group and features a unique buckled honeycomb lattice of osmium. It exhibits long-range antiferromagnetic ordering with a high Néel temperature of 385 K as confirmed by susceptibility, heat capacity, and neutron diffraction measurements and is electrically insulating. This compound is also the first example of a 2:1-ordered osmate perovskite. Theoretical investigations indicate that Sr3CaOs2O9 features a sizeable antiferromagnetic exchange between the puckered planes resulting in a high TN. The magnetic properties of the known compound Sr3CaRu2O9 are elucidated in comparison. It shows antiferromagnetic order below TN ≈ 200 K.
CRIS-Team Scopus Importer:2023-03-20